Relationship between the knowledge, attitude, and practices on online food delivery (OFD) and the nutritional status of UP Diliman (UPD) dormers - Lao, Lara Mei U.; Monana, Joecile Faith; Xu, Shara Cindy N.
The use of online food delivery (OFD) has significantly increased in recent years, despite studies finding a link to the development of undesirable eating habits. There is still limited research and tools for measuring nutrition knowledge, attitudes towards OFD use, and practices of OFD use, as well as the relationship between and among them, and their impact on nutritional status. This study aimed to determine the current knowledge, attitude, and practices (KAP) of dormers residing on the University of the Philippines Diliman (UPD) campus and to investigate its relationship with body mass index (BMI) as an indicator of nutritional status. A descriptive quantitative research design was employed through a pre-tested self-administered questionnaire. A moderate reliability was achieved in the Knowledge and Attitude section of the questionnaire with a KR-2 score of 0.510 and Cronbach’s alpha of 0.71, respectively. There were a total of 146 eligible respondents, and the findings show that they possess high nutritional knowledge (mean score 73%), positive attitudes (mean score 87%), and frequently use OFD (2-3 times per week). However, only a weak relationship was found between these constructs and BMI. Nonetheless, findings observed undesirable food behaviors and habits among dormers. Social factors also influence ordering habits, with most dormers ordering with friends (52%) and other dormers (50%). Although dormers understand basic nutrition concepts, their food choices are still heavily influenced by convenience and time-saving factors, which often prevent them from selecting healthier options.